Victor D. Sanua (1920-2009) and Inter-American Society of Psychology - León Donayre, Ramón (2024)
This communication presents the biography and scientific contribution, as well as the institutional role of Victor D. Sanua (1920-2009), an important figure in psychology. Sanua served for several years as director of the Inter-American Society of Psychology (SIP), the most important society of Spanish- and Portuguese-speaking Latin American psychologists, which also includes numerous North American and European psychologists. In addition to presenting Sanua’s work at the SIP, his contribution to psychological research is also analyzed.